1968
DOI: 10.1063/1.1656634
|View full text |Cite
|
Sign up to set email alerts
|

High-Homogeneity Tape-Wound Superconducting Coil

Abstract: A 100 kG superconducting magnet with field uniformity better than 1 part in 104 over a 1 cm diam sphere has been constructed from composite Nb3Sn superconducting tape. Data showing the performance of the coil are presented. The field profiles depend both on the magnitude of the field and on the field history; field uniformity is considerably reduced at low fields after an excursion to higher fields, because of trapped flux. Neither the field nor the field profile at a given current agrees with the values calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While the screening field is negligible in magnets built with modern LTS multifilamentary wires, the first superconducting magnets built over 40 years ago employed V 3 Ga and Nb 3 Sn tapes, whose architecture is similar to that of modern coated conductors. It was found that the field generated by those earlier superconducting magnets was lower than the expected value and dependent upon the operational history [5,[8][9][10]. The residual magnetic field after de-charging the magnet was also measured along the axis [9], and it was found to increase from the centre to the coil ends.…”
Section: Introductionmentioning
confidence: 92%
“…While the screening field is negligible in magnets built with modern LTS multifilamentary wires, the first superconducting magnets built over 40 years ago employed V 3 Ga and Nb 3 Sn tapes, whose architecture is similar to that of modern coated conductors. It was found that the field generated by those earlier superconducting magnets was lower than the expected value and dependent upon the operational history [5,[8][9][10]. The residual magnetic field after de-charging the magnet was also measured along the axis [9], and it was found to increase from the centre to the coil ends.…”
Section: Introductionmentioning
confidence: 92%